PENGARUH UKURAN PERUSAHAAN, TIPE INDUSTRI, DAN INTENSITAS RESEARCH AND DEVELOPMENT PADA PENGUNGKAPAN MODAL INTELEKTUAL - Astuti, Ni Made Ari; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 15 No 1 (2016), 2016)
The research purpose is to analyze the effect of firm size, industry type and intensity of research and development on the disclosure of intellectual capital. Company size, industry type and intensity of research and development is the independent variable and the dependent variable is the disclosure of intellectual capital. The population was companies listed on the Indonesian Stock Exchange. Stratified random sampling method is used as the sampling techniques. The minimum sample is obtained by the Slovin formula by 84 companies. The data analysis using descriptive statistics, the classic assumption test and multiple linear regression analysis. Descriptive statistical analysis showed that the average intellectual capital information disclosed by companies in Indonesia amounted to only 43,15%. The research results prove the company size and industry type significant influence on the disclosure of intellectual capital. While the variable intensity of research and development has no effect on the disclosure of intellectual capital.
Keywords: disclosure, intellectual capital, company size